Neonatal Sepsis and Associated Pathogens in Raipur Institute of Medical Sciences and Hospital - Kurrey, Dr. Ram Manohar (International Journal of Innovative Research in Medical Science, 2018)
Introduction Neonatal sepsis is defined as a clinical syndrome in an infant 28 days of life or younger, manifested by systemic signs of infection and isolation of a bacterial pathogen from the bloodstream.[1] Neonatal sepsis is one of the leading causes of morbidityand mortality both among term and preterm infants in spite of recent advances in health care units.[2] The majority of these deaths occur in low-income countries i.e. developing and under developed countries and almost 1 million of these deaths are attributed to infectious causes including neonatal sepsis, meningitis, and pneumonia.[3] There is significant contribution of sepsis to mortality and morbidity among very-low-birth-weight (VLBW, <1500 g) infants in Neonatal Intensive Care Units (NICUs).[4] Neonatal sepsis present in nonspecific form hence diagnosis and management of sepsis are a great challenge facing neonatologists in NICUs. These sign and symptoms include fever or hypothermia, respiratory distress including cyanosis and apnea, feeding difficulties, lethargy or irritability, seizures, hypotonia bulging fontanel, bleeding problems, poor perfusion abdominal distention, gauiac-positive stools, hepatomegaly unexplained jaundice etc.[5,6] Clinical diagnosis of neonatal sepsis is difficult due to nonspecific signs and symptoms and laboratory diagnosis is lengthy and time consuming. Due to this clinician starts the empirical antibiotic therapy till the suspected sepsis is ruled out and increased multidrug resistant organisms make the treatment less effective and treatment is delayed.[7] Neonatal sepsis is generally caused by Gram-positive and Gram-negative bacteria and Candida. As sepsis is a systemic inflammatory response to infection, isolation of bacteria from blood is considered as gold standard for the diagnosis of sepsis.[8] but it takes 24–48 hours for results. Also less blood is available for Inoculation (0.5–1.0 ml) which decreases its sensitivity, as approximately 60–70% of infants have a low level of bacteraemia.[9]